Denesting An Interesting Radical

Поделиться
HTML-код
  • Опубликовано: 7 ноя 2024

Комментарии • 9

  • @pwmiles56
    @pwmiles56 11 часов назад +1

    Fiendish! In the end I just factorised out sqrt(5) within the main radical leaving 6+2sqrt(5), easy to guess as the square of 1+sqrt(5). NB there is a radical missing at the end of Method 1, it does actually work.

  • @forcelifeforce
    @forcelifeforce 11 часов назад +3

    *@ SyberMath* -- You can let a + b*sqrt(5) = 10 + 6sqrt(5).
    Square each side:
    Then a^2 + 5b^2 = 10 and
    2ab = 6sqrt(5).
    ab = 3 or b = 3/a.
    From these we get a^4 - 10a^2 + 45 = 0.
    a^2 = 5 +/- 2isqrt(5)
    I'll use a^2 = 5 + 2isqrt(5).
    So, a = sqrt[5 + 2isqrt(5)].
    b*sqrt(5) = 3sqrt(5)/a = 3sqrt(5)/sqrt[5 + 2isqrt(5)] = sqrt[5 - 2isqrt(5)].
    a = (1/2 + i/2)5^(1/4)[sqrt(5) - i]
    and b = (1/2 + i/2)[5^(1/4) - i(125)^(1/4)].
    a + b*sqrt(5) = 125^(1/4) + 5^(1/4)

    • @SyberMath
      @SyberMath  9 часов назад

      Wow! That’s good

  • @NadiehFan
    @NadiehFan 5 часов назад

    This is known as _indirect denesting_ of a nested square root.
    Generally, a nested square root √(a ± b√c) where a, b, c are positive _rational_ numbers and √c is _irrational_ can be denested directly, that is, there exist positive rational numbers p and q such that √(a ± b√c) = √p ± √q, _if and only if_ a² − b²c is the square of a rational number.
    If √(a + b√c) and where a, b, c are rational numbers such that a + b√c is a positive real number and √c is irrational then we can take out a factor √c which gives
    √(a + b√c) = √(√c·(a/√c + b)) = √(√c)·√(a/√c + b) = ⁴√c·√(b + a/√c)
    We can now consider two cases. If a > 0 we have
    √(a + b√c) = ⁴√c·√(b + a/√c) = ⁴√c·√(b + √(a²/c))
    and if a < 0 we have
    √(a + b√c) = ⁴√c·√(b + a/√c) = ⁴√c·√(b − √(a²/c))
    Assuming b is positive, √(b ± √(a²/c)) can be denested directly, that is, there exist positive rational numbers p and q such that √(b ± √(a²/c)) = √p ± √q, _if and only if_ b² − a²/c is the square of a rational number and this is therefore the criterion for the _indirect denestibility_ of √(a + b√c) where a, b, c are rational numbers such that a + b√c is a positive real number and √c is irrational.
    For √(10 + 6√5) we have a = 10, b = 6, c = 5 and therefore a² − b²c = 100 − 36·5 = −80 which is not the square of a rational number. Therefore, √(10 + 6√5) cannot be denested directly, that is, there exist no positive rational numbers p and q such that √(10 + 6√5) = √p + √q. However, we _do_ have b² − a²/c = 36 − 100/5 = 16 which _is_ the square of a rational number. So, √(10 + 6√5) _can_ be denested indirectly, that is, there exist rational numbers p and q such that √(10 + 6√5) = ⁴√5·√(6 + 2√5) = ⁴√5·(√p + √q).
    Since 6² − (2√5)² = 36 − 20 = 16 is the square of a rational number, √(6 + 2√5) can be denested directly and is equal to √5 + 1, so we have
    √(10 + 6√5) = ⁴√5·√(6 + 2√5) = ⁴√5·(√5 + 1) = ⁴√5·(⁴√25 + 1) = ⁴√125 + ⁴√5
    Note that since √(6 − 2√5) = √5 − 1 we also have
    √(−10 + 6√5) = ⁴√5·√(6 − 2√5) = ⁴√5·(√5 − 1) = ⁴√5·(⁴√25 − 1) = ⁴√125 − ⁴√5
    For a full discussion, including proofs, I recommend reading the paper _On the denesting of nested square roots_ by Eleftherios Gkioulekas which is freely available and can easily be found if you google it. I cannot give a direct link here because RUclips will then remove this message.

  • @guyhoghton399
    @guyhoghton399 2 часа назад

    I find it easier to remember that
    _√(a ± b√n) = |t₁ ± t₂|_
    where _t₁_ and _t₂_ are the roots of the quadratic
    _t² - at + ¼b²n = 0_

  • @scottleung9587
    @scottleung9587 10 часов назад

    Nice!

  • @赖皮球
    @赖皮球 12 часов назад

    sqrt(6*5+2sqrt(125))/sqrt(5)=(5+sqrt(5))/sqrt(5)=sqrt(5)+1

  • @giuseppemalaguti435
    @giuseppemalaguti435 11 часов назад +1

    =√((3+√5)^2-4)=√((5+√5)(1+√5))=√(√5(1+√5)(1+√5))=(√√5)(1+√5)

  • @Don-Ensley
    @Don-Ensley 8 часов назад

    problem
    De-nest √(10+6√5)
    First let's simplify by factoring out√(2√5).
    √(10+6√5) =√(2√5) √(3+√5)
    After we de-nest √(3+√5) the answer will be the de-nested form of √(3+√5) times √(2√5).
    De-nesting √(3+√5)
    √(3+√5) = a + b √5
    Square both sides.
    3 + √5 = a² +5b² +2ab√5
    3 = a² +5b²
    2ab = 1
    4 a² b² = 1
    a² = 1/(4 b²)
    3 = 1/(4 b²) + 5 b²
    12 b² = 1 + 20 b⁴
    20 b⁴ - 12 b² + 1 = 0
    b ² = [ 12 ± √(144-4•20) ] / 40
    = [ 12 ± 8 ] / 40
    = 1/2, 1/10
    a² = 1/(4 b²)
    = 1/2, 5/2
    a,b = 1/√2, 1/√2
    √(3+√5) = 1/√2 + √5/√2
    = (1+√ 5)/√2
    This is a correct de-nesting of √(3+√5).
    Therefore
    √(10+6√5) =√(2√5) (1+√ 5)/√2
    = ∜5 + ∜5 √5
    is the de-nested form of √(10+6√5) .
    answer
    ∜5 + ∜5 √5